Designing E-Commerce For Umkm Ried Kantongku Based On A Website Using Laravel Framework (JESII: Journal of Elektronik Sistem InformasI, 2023)
With the rapid development of the internet, many companies are utilizing it to market their products, expanding their marketing reach. There are small and medium-sized enterprises (UMKM) in Bandung that still follow conventional selling methods, such as Ried Kantongku UMKM, which operates in the field of fashion bags. However, in this digital era, UMKM entrepreneurs are urged to adapt to technological advancements. One of the efforts that can be made is to engage in digital marketing by creating a website for selling their products. Therefore, considering the various issues in this research, a web-based application will be developed to facilitate the digitalization of the sales process. The framework used for this will be Laravel, and the programming languages employed will be HTML, PHP, and Javascript. The database will be PostgreSQL/XAMPP.